Repeat Head CT for Expectant Management of Traumatic Epidural Hematoma - Flaherty, Brian F; Moore, Hannah E; Riva-Cambrin, Jay; Bratton, Susan L (Pediatrics (Evanston), 2018)
Guidelines regarding the role of repeated head computed tomography (CT) imaging in the nonoperative management of traumatic epidural hematomas (EDHs) do not exist. Consequently, some children may be exposed to unnecessary additional ionizing radiation. We describe the frequency, timing, and utility of reimaging of EDHs to identify patients who might avoid reimaging. A retrospective cohort study of subjects aged 0 to 18 years with a traumatic EDH treated at a level I pediatric trauma center from 2003 to 2014. Radiographic and clinical findings, the frequency and timing of reimaging, and changes in neurologic status were compared between subjects whose management changed because of a meaningful CT scan and those whose did not. Of the 184 subjects who were analyzed, 19 (10%) had a meaningful CT. There was no difference in the frequency of CT scans between the meaningful CT scan and no meaningful CT groups (median 1 [interquartile range 1-2] in no meaningful CT and median 1 [interquartile range 1-2] in meaningful CT scans; = .7). Only 7% of repeated CTs changed management. Neurologic status immediately before the repeat scan (odds ratio 45; 95% confidence interval 10-200) and mass effect on the initial CT (odds ratio 4; 95% confidence interval 1.5-13) were associated with a meaningful CT. Reimaging only subjects with concerning pre-CT neurologic findings or mass effect on initial CT would have decreased imaging by 54%. Reimaging is common, but rarely changes management. Limiting reimaging to patients with concerning neurologic findings or mass effect on initial evaluation could reduce imaging by >50%.